Analysis of Mullerian developmental defects in a tertiary care hospital: a four year experience - Patel, Swati N.; Desai, Ajesh N.; Pamnani, Dirgha H.; Modi, Komal P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Mullerian duct anomalies are congenital anomalies of the female genital tract. Mullerian duct anomalies affect the reproductive health of the female to a varied extent. This may present as obstructive or as non-obstructive anomalies. When clinically suspected, proper investigations are required to confirm the diagnosis including ultrasonography, laparoscopy and hysteroscopy. Methods: In the present study, all the patients presenting with Mullerian duct anomalies to the gynaecology OPD at General Hospital, Sola, GMERS Medical College, Ahmedabad during the four year duration from 2011 to 2014 were included. These patients were analysed with respect to their incidence, presenting complain, age at presentation, classified according to AFS classification after proper diagnosis and managed individually. Results: The incidence of Mullerian duct anomalies was found to be 0.084%.52.9% belonged to the age group of 21 to 25 years. Most of these patients (73.5%) presented with chronic complains. Only a few presented with acute symptoms (14.7%) whereas a few were asymptomatic (11.8%). Septate uterus (20.6%) was the most common anomaly diagnosed at our setup followed by bicornuate uterus (17.7%) and tansverse vaginal septum (17.6%). History along with clinical and USG examination were adequate in diagnosis of patients with vaginal agenesis, didelphic, bicornuate uterus, TVS and imperforate hymen. Laparoscopy was needed to confirm cases of MRKH & unicornuate uterus and hysteroscopy for cases of septate uterus. Arcuate uterus was diagnosed during LSCS. Conclusions: It was thus concluded that with timely evaluation, diagnosis and optimal management, their menstrual disturbances are relieved early in adolescence period recuperating their psychiatric health & improving their reproductive carrier. Delay in management may cause serious complications and potential infertility.